Cyclooxygenase-2 Expression in Squamous Cell Carcinoma of the Head and Neck - Mozhgan Mokhtari; Pegah Hedayat (مجله دانشکده پزشکی اصفهان, 2017)
Background: Cyclooxygenases-2(COX) expression in cancer tissues is associated with worse prognosis of cancers. We studied cyclooxigenase-2 expression among patients with head and neck squamous cell carcinoma (HNSCC).